Potential applications of portland cement on bone tissue engineering. Phase I: biocompatibility studies–calcium hydroxide effects - Daniel Gallego; Luis Ernesto López; Derek Hansford; Jonas Klemas (Revista Facultad de Ingeniería Universidad de Antioquia, 2006)
There is an increasing and unfulfilled demand of bone substitutes with optimal mechanical and biological properties. Based on the excellent mechanical and structural properties of Portland Cement, a biocompatibility exploratory study of this material was proposed. Plain substrates were fabricated with Gray Type I Portland Cement under different conditions (Neutralized-SN, Carbonated-SC, not neutralized-SnN), which were then used to conduct a Direct Contact Assay with CHO and HOS cells for 24h. The substrates were characterized by SEM, and phenolphthalein assays to determine the pH value, while the cell culture assays were evaluated by Phase Contrast Microscopy. The results show that SnN had the highest pH value (> 12,0), followed by SN, and finally by SC (≈ 7,4); it was also observed that the cytotoxicity of the substrates diminished in proportion to the pH value. It is proposed that the cytotoxicity of Portland Cement is caused by the Ca(OH)2 formed during the hydration of this material. Thus, by lowering the amount of Ca(OH)2, either by carbonation or neutralization, the biocompatibility of the material is positively affected.